Error Analysis of Written Compositions of Tertiary Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
Writing is one of the most complex skills; thus, an individual needs the necessary competencies to produce acceptable output for effective writing. Therefore, pre-service teachers should be equipped with excellent writing skills. They will be tasked to prepare paperwork, memoranda, correspondences, and lesson plans and, sometimes, act as school papers and research advisers.Using documentary analysis, this study assessed the writing competence of the pre-service teachers enrolled in Union Christian College during the first semester of the school year 2022-2023. It utilized the descriptive research design. The data used in the analysis is a compilation of 70 English composition manuscripts obtained from a dataset. It was analyzed using Grammarly. Frequency count was used in the management of data.The results showed that the pre-service teachers' writing competence is unsatisfactory, with significant correctness, clarity, engagement, and delivery issues.It is then recommended that pre-service teachers should undergo the formulated training program for writing enhancement.
Keywords: composition analysis; pre-service teachers; writing competence